U.S. Latina Age of Sexual Debut: Long-term Associations and Implications for HIV and Drug Abuse Prevention - Dillon, Frank R. (2010)
This cross-sectional study explored associations among (a) age of sexual debut, (b) drug abuse, and (c) sexual risk behaviors among an urban community based sample of 158 predominantly immigrant, Latina adults. Time in the United States and having a mother who used drugs during the participants' childhood or adolescence were significantly related to age of sexual debut. In turn, younger ages of sexual debut were associated with drug abuse and more sexual risk behaviors (greater number of sexual partners, more frequent alcohol and drug use before or during sex, greater levels of intoxication from alcohol or drugs during sex). Implications for HIV/AIDS and drug abuse clinical services and future research with U.S. Latina populations are discussed.